Development of Laboratory as the Center of Mikrotik Certification Preparation - Budi Nugroho; Henni Endah Wahanani; Eva Yulia Puspaningrum (Future Science)
One of the important competencies in the field of Information and Communication Technology (ICT) is Computer Network (which includes the development of Information Technology infrastructure and computer network security). One part of competence in the Computer Network scope is the use of Mikrotik equipment that is needed in the practical field. Currently, many agencies and industries whose computer network infrastructure use Mikrotik-based devices. The development of activity program that leads students to the preparation of this competency is clearly necessary. With regard to the competence of Mikrotik's own expertise, the existence of a Mikrotik certificate becomes proof that someone has mastered this competency. To get this certificate, of course, must follow the Mikrotik Certification program which cost is relatively expensive. In addition, this certification program is quite difficult to pass. So anyone who wants to follow this certification needs preparation adequately. The grant program of UPN